2015
DOI: 10.1051/0004-6361/201425398
|View full text |Cite
|
Sign up to set email alerts
|

Ion irradiation of the Murchison meteorite: Visible to mid-infrared spectroscopic results

Abstract: Aims. The goal of this study is to simulate space weathering processes on primitive bodies. We use ion implantation as a simulation of solar wind irradiation, which has been suggested by several authors to be the major component of space weathering on main belt asteroids. The laboratory analogs we irradiate and analyze are carbonaceous chondrites; we started the study with the Allende CV meteorite and in this companion paper we present results on the Murchison CM meteorite. Methods. We performed irradiations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
49
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 57 publications
13
49
1
Order By: Relevance
“…Thus, the spectral bluing trends of this sample may be representative of asteroids that have experienced small degrees of alteration. Additionally, Lantz et al (2015b) found a broad correlation between the spectral evolution of meteorites and their initial albedos and possibly carbon content. While a much larger set of experiments are still needed to constrain the spectral trends of volatile-rich CCs, the data presented here along with the Lantz et al (2015b) study appear to indicate that the compositional dependency of space weathering trends may be a useful tool to constrain the compositions and aqueous histories of volatile-rich asteroids.…”
Section: Comparison To Space Weathering Trends On Volatile-rich Astermentioning
confidence: 91%
“…Thus, the spectral bluing trends of this sample may be representative of asteroids that have experienced small degrees of alteration. Additionally, Lantz et al (2015b) found a broad correlation between the spectral evolution of meteorites and their initial albedos and possibly carbon content. While a much larger set of experiments are still needed to constrain the spectral trends of volatile-rich CCs, the data presented here along with the Lantz et al (2015b) study appear to indicate that the compositional dependency of space weathering trends may be a useful tool to constrain the compositions and aqueous histories of volatile-rich asteroids.…”
Section: Comparison To Space Weathering Trends On Volatile-rich Astermentioning
confidence: 91%
“…Most commonly, space weathering produces a reddening and a darkening of the surface (Brunetto et al, ). However, it has been shown that these effects are not systematic for every asteroid class but depends also on the initial albedo (Lantz et al, ). Thus, the darkest C‐type asteroids (the richest in carbon) can have the opposite spectral behavior with respect to space weathering, that is, bluing and brightening.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the Tagish Lake meteorite, which is darker (albedo between ≃2.0 and 3.5% at 550 nm); (Izawa et al, 2015) and contains even more carbon than LRM (5.5% wt. (Lantz et al, 2015)), becomes brighter and bluer after irradiation. Therefore, the LRM of Mercury is an intermediate case between the cases of Murchison meteorite and Tagish Lake meteorite and thus can darken and redden when exposed to the space weathering.…”
Section: 1029/2019je005932mentioning
confidence: 99%
See 2 more Smart Citations